Ketoprofen, an emerging photoallergen - Zuba, Ewelina Bogumiła; Osmola-Mańkowska, Agnieszka; Jenerowicz, Dorota; Stawny, Maciej; Czarnecka-Operacz, Magdalena (Journal of Medical Science, 2014)
Introduction. Ketoprofen, which belongs to the group of non-steroidal anti-inflammatory drugs (NSAIDs), is an emerging photoallergen. Especially its topical use may be a cause of drug-induced photosensitivity.Material and methods. We report two cases of photoallergic and one case of phototaggravated contact dermatitis due to topical ketoprofen application, confirmed by photopatch testing.Results. All patients presented positive reactions to ketoprofen at an irradiated site. Only one patient demonstrated a positive reaction to ketoprofen both at an irradiated and non-irradiated site.Conclusions. Photosensitive reactions due to topical application of ketoprofen being of significant clinical importance need to be properly diagnosed. It is crucial to provide patients with a detailed instruction how to protect photoexposed areas during therapy with ketoprofen.